How do you find the integral of #(e^(-x))(cos(2x))#?

Answer 1

#int e^(-x)cos(2x) dx = e^(-x)/5 (-cos(2x) + 2 sin(2x)) + cst#

Use complex numbers. Write #cos(2x) = Re(e^(i 2 x))# So, #int e^(-x) cos(2x) dx = Re int e^(-x)e^(i 2 x) dx = Re int e^((-1+2i)x) dx#
Now it's easy to integrate because you know that if #a ne 0#, #int e^(ax) dx = 1/a e^(ax) + cst#. So :
#int e^(-x)cos(2x) dx = Re(1/(-1+2i) e^((-1+2i)x)) + cst#
After that, you have to simplify #1/(-1+2i) e^((-1+2i)x)# : # e^(-x)/(-1+2i) = e^(-x)(cos(2x) + i sin(2x))/(-1+2i)#
Multiply by #(-1-2i)# everywhere and use the fact that #(a-bi)(a+bi) = a^2+b^2# :
#(cos(2x) + i sin(2x))/(-1+2i) = ((cos(2x) +i sin(2x))(-1-2i))/(1+4)#

Keep only the real part :

#Re((cos(2x) + i sin(2x))/(-1+2i)) = (-cos(2x) + 2 sin(2x))/5#

Finally,

#int e^(-x)cos(2x) dx = e^(-x)/5 (-cos(2x) + 2 sin(2x)) + cst#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To find the integral of ( e^{-x} \cdot \cos(2x) ), you can use integration by parts. The integration by parts formula is:

[ \int u , dv = uv - \int v , du ]

Let: [ u = e^{-x} ] [ dv = \cos(2x) , dx ]

Then: [ du = -e^{-x} , dx ] [ v = \frac{1}{2} \sin(2x) ]

Now, plug these into the integration by parts formula:

[ \int e^{-x} \cdot \cos(2x) , dx = e^{-x} \cdot \frac{1}{2} \sin(2x) - \int \frac{1}{2} \sin(2x) \cdot (-e^{-x}) , dx ]

This simplifies to: [ = \frac{e^{-x}}{2} \sin(2x) + \frac{1}{2} \int e^{-x} \sin(2x) , dx ]

Now, to integrate ( \int e^{-x} \sin(2x) , dx ), you can use integration by parts again:

Let: [ u = e^{-x} ] [ dv = \sin(2x) , dx ]

Then: [ du = -e^{-x} , dx ] [ v = -\frac{1}{2} \cos(2x) ]

Plug these into the integration by parts formula:

[ \int e^{-x} \sin(2x) , dx = -e^{-x} \cdot \frac{1}{2} \cos(2x) - \int \frac{1}{2} \cos(2x) \cdot (-e^{-x}) , dx ]

[ = -\frac{e^{-x}}{2} \cos(2x) - \frac{1}{2} \int e^{-x} \cos(2x) , dx ]

Now, let's bring the ( \int e^{-x} \cos(2x) , dx ) term to the other side:

[ \frac{3}{2} \int e^{-x} \cos(2x) , dx = \frac{e^{-x}}{2} \sin(2x) - \frac{e^{-x}}{2} \cos(2x) ]

[ \int e^{-x} \cos(2x) , dx = \frac{2}{3} \left( \frac{e^{-x}}{2} \sin(2x) - \frac{e^{-x}}{2} \cos(2x) \right) + C ]

[ = \frac{e^{-x}}{3} \sin(2x) - \frac{e^{-x}}{3} \cos(2x) + C ]

So, the integral of ( e^{-x} \cos(2x) ) is ( \frac{e^{-x}}{3} \sin(2x) - \frac{e^{-x}}{3} \cos(2x) + C ), where ( C ) is the constant of integration.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7